Chemical modification of chitosan in the absence of solvent for diclofenac sodium removal: pH and kinetics studies - Pereira,Kerlaine Alexandre Araújo (2014)
Chitosan was modified with acetylacetone and ethylenediamine in the absence of solvent. The new biopolymer obtained from the modification was characterized by elemental analysis and NMR 13C and applied in the removal of diclofenac sodium aqueous solution varying the pH and time. Through elemental analysis was possible to verify a decreasing in C/N relation after reaction with acetylacetone and an increasing after modification with ethylenediamine. From NMR analysis was verified the appearance of peaks around 160-210 ppm in both materials due to free carbonyl groups in the first step of the modification, besides the formation of imine bonds. The adsorption tests showed that the highest value occurred at pH 4 and from the results of the kinetic study was found that maximum adsorption occurred within 45 minutes and experimental data adjusted better to linear adjustment, following pseudo second-order model. The results show a material efficient in the removal of emerging pollutants.